Cultural Dynamics and Ethical Marketing: Balinese Values and Consumer Trust in Hospitality SMEs - Nurfadhilah, Nurfadhilah; Tijang, Bakhtiar; Hafiz, Khalilah Binti Abd; Ikhrami, Siti Mirna (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This study explores the influence of cross-cultural factors on ethical marketing practices and consumer trust, with Balinese cultural values serving as a moderating force among hospitality MSMEs in Bali. We weave Hofstede’s cultural dimensions with Tri Hita Karana, and offer a fresh perspective on how global ethical frameworks resonate within local spiritual contexts. A quantitative explanatory design was applied using data from 200 respondents analyzed through Partial Least Squares–Structural Equation Modeling. The results indicate that cultural orientations shape ethical marketing, which subsequently strengthens consumer trust, while Balinese values deepen this connection. The study enriches the understanding of how ethical behavior is interpreted across cultural boundaries and grounded in indigenous wisdom. The findings provide strategic guidance for MSMEs to cultivate enduring consumer trust and promote sustainable growth in culture-based tourism environments.